2012
DOI: 10.1002/cncr.27654
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD40 ligand (sCD40L) provides a new delivery system for targeted treatment

Abstract: sCD40L-based chimeric proteins were able to bind and internalize into B cells that expressed the CD40 receptor and specifically and efficiently induced apoptotic death. Moreover, the current results validated for the first time the ability of sCD40L to serve as a direct delivery system for targeted molecules. sCD40L-based chimeric cytotoxic proteins offer a new weapon in the everlasting war against cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…sCD40L retains the trimeric structure of the full-length protein and its biological functions (37). The sCD40L was able to bind and internalize into B cells that expressed the CD40 receptor and specifically and efficiently induced apoptotic death (38). In the 1990, MacDonald et al (39) reported that trimeric sCD40L was able to inhibit apoptosis induced by the combination of agonists to a certain degree, but such rescue proved to be short-lived.…”
Section: Discussionmentioning
confidence: 99%
“…sCD40L retains the trimeric structure of the full-length protein and its biological functions (37). The sCD40L was able to bind and internalize into B cells that expressed the CD40 receptor and specifically and efficiently induced apoptotic death (38). In the 1990, MacDonald et al (39) reported that trimeric sCD40L was able to inhibit apoptosis induced by the combination of agonists to a certain degree, but such rescue proved to be short-lived.…”
Section: Discussionmentioning
confidence: 99%